Three dimensions of the linguistic sign and three types of schizophasia - Woźniak, Tomasz (Papers in Linguistics, 2024)
The aim of this article is to provide a typology of linguistic disorders occurring in the course of schizophrenic psychosis. Analyses of utterances made by people suffering from schizophrenia prove that there occur different types of phenomena causing textual incoherence. Linguistic interpretation of texts affected by schizophasia selected from the corpus, in conjunction with the conclusions based on clinical research, allows one to distinguish three basic types of linguistic behavioural disorders in schizophrenia – the disorganised type, the delusional type and the schizophatic text impoverishment type. Furthermore, everyday practice points to the existence of mixed types of schizophasia, in all possible combinations of the three variants, which is a phenomenon analogous to the problems observed in the diagnosis and classification of aphasia. Linguistic conclusions are confirmed by studies on the functioning of particular brain areas, taking into account the site of language disorders in a given schizophrenic syndrome.